Operationalizing the Quality of Teacher Education Institutes: Principles and Challenges - Khandpur, Nimrat KD (Voices of Teachers and Teacher Educators, 2018)
The paper briefly reviews the issues and challenges related to the quality of teacher education in India. It then traces efforts towards assessment and accreditation of teacher education institutes with specific reference to National Council of Teacher Education (NCTE) and National Assessment and Accredition Council (NAAC), highlighting major critique of the same. A discussion of what the purpose of accreditation should and how this purpose can be achieved is followed by a recommendation for a comprehensive, developmental framework for assessment of teacher education institutes which can be used for self-assessment by the institute and accreditation by an external body. The development of such a framework is illustrated with a discussion of challenges inherent in such a task, and the principles that emerge.